Rethinking the decision-making process to treat gingival recession associated with non-carious cervical lesions - Santamaria, Mauro Pedrine [UNESP]; Mathias-Santamaria, Ingrid Fernandes [UNESP]; Ferraz, Laís Fernanda Ferreira [UNESP]; Casarin, Ren'to Corrê‘ Vi'n’; Romito, Giuseppe Alex'ndre; Sallum, Enilson Antônio; Pini-Prato, Giovan Paolo; Casati, Márcio Zaffalon (FapUNIFESP (SciELO), 2021)
The presence of a tooth-surface defect, such as a non-carious cervical lesion (NCCL), associated with sites of gingival recession (GR) defects creates a combined soft tissue/tooth defect (CD) that requires a different treatment plan. This study aimed to critically review the literature regarding the available treatment protocols for CDs and suggest a new decision-making process. NCCLs were classified as Class A-: the cementoenamel junction (CEJ) was visible and the root surface discrepancy was < 0.5 mm (no step); Class A+: CEJ was visible and the root surface discrepancy was > 0.5 mm (with a step); Class B-: unidentifiable CEJ without a step; Class B+: unidentifiable CEJ with a step. NCCLs affecting both root and crown surfaces (Class B) lead to CEJ destruction and consequently eliminate an important landmark used before and after root coverage procedures. The depth of the root surface discrepancy is vital owing to its possible impact on soft tissue adaptation after healing, which, in turn, may influence the treatment options, namely the use of graft and/or composites to compensate for the discrepancy. Clinically, a step with horizontal depth greater than 0.5 mm should be recognized as the minimum threshold value to define this condition. Extremely deep defects tend to assume a V-shaped topography. Therefore, extremely deep V-shaped defects were classified into subclasses A+V, a V-shaped defect, and B+V, a V-shaped defect with loss of CEJ, for management considerations. The treatment options, supported by the literature, and a decision-making process to deal with each condition are presented.
Keywords: Clinical Decision-Making; Dentin Sensitivity; Gingival Recession; Tooth Abrasion; Tooth Cervix; Tooth Root